Omega‐Shaped Variant of the Umbilical Artery: Prenatal Diagnosis and Outcome. (1st March 2013) - Shen, Ori; Rabinowitz, Ron; Malinger, Gustavo; Mazaki, Eyal; Tsafrir, Avi
Abstract : The purpose of this series was to report on the observation of an anomalous course of the umbilical artery. Ten cases in a 25‐month period are reported. An omega‐shaped variant, coined the "omega sign, " of one of two umbilical arteries or of a single umbilical artery was observed. In 2 cases, there were two umbilical arteries, one of them with the anomalous vessel. In 8 cases, the vessel was a single umbilical artery. In 1 case with a single umbilical artery and pericardial effusion, aneuploidy was found on amniocentesis. A second case was associated with multiple anomalies. A third case was associated with hypoplastic left heart syndrome. Seven cases with the omega sign as an isolated finding, with or without a single umbilical artery, had favorable outcomes. An omega‐shaped variant of the umbilical artery is likely to be more common in cases of a single umbilical artery than in cases with two umbilical arteries. It is probably a normal variant when unassociated with additional sonographically detectable structural anomalies.